Knowledge, attitude and awareness of photodynamic therapy among orthodontic practitioners: A questionnaire-based survey - Javed Sodawala (Bioinformation, 2026)
Photodynamic therapy (PDT) is a minimally invasive light-based treatment with antimicrobial applications relevant to orthodontic care. Therefore, it is of interest to assess the knowledge, attitudes, awareness and perceptions of PDT among 153 orthodontic practitioners using a 28-item questionnaire with good reliability (Cronbach's alpha = 0.82). Most respondents were younger than 30 years (65.4%) and had less than 4 years of experience (66%), while 88.9% scored above 8/10 for knowledge and 92.16% correctly identified the PDT mechanism. Awareness of PDT's role in antibiotic resistance was 82.35%, 66.7% favored its inclusion in postgraduate curricula and 58.2% identified equipment cost and technical requirements as barriers. Orthodontic practitioners therefore showed strong knowledge and favorable attitudes toward PDT, but structured training and curricular integration may facilitate routine clinical adoption.